2020
DOI: 10.1093/rap/rkaa013
|View full text |Cite
|
Sign up to set email alerts
|

Use of rheumatoid arthritis impact of disease (RAID) in routine care; identification of DAS28 remission and unmet patient-reported outcomes

Abstract: Objective The aim was to assess how the patient-reported outcome RA impact of disease (RAID) relates to DAS28 categories in routine care, its utility in identifying patients in DAS28 remission (RDAS) or low disease activity (LDAS) and the burden of unmet patient-reported needs in those achieving RDAS/LDAS. Methods DAS28 and RAID scores were collected from patients with established RA attending for routine review. The relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The RAID scores correlated strongly with the DAS28 when calculated with the erythrocyte sedimentation rate (DAS28-ESR) or the C-reactive protein concentration (DAS28-CRP) and also correlated with the patient global assessment (PGA) component of the DAS28 composite score 1 . Notably, the PGA covers two concepts -global health and overall disease activity -and is the PRO incorporated into most of the ACR-endorsed and EULARendorsed RA assessment tools.…”
Section: Peter C Taylormentioning
confidence: 95%
See 4 more Smart Citations
“…The RAID scores correlated strongly with the DAS28 when calculated with the erythrocyte sedimentation rate (DAS28-ESR) or the C-reactive protein concentration (DAS28-CRP) and also correlated with the patient global assessment (PGA) component of the DAS28 composite score 1 . Notably, the PGA covers two concepts -global health and overall disease activity -and is the PRO incorporated into most of the ACR-endorsed and EULARendorsed RA assessment tools.…”
Section: Peter C Taylormentioning
confidence: 95%
“…explored using mixed-effects linear regression. Mistry et al 1 found that both the patient global visual analogue scale and the square root tender joint count were strongly associated with RAID scores (P < 0.01). Importantly, of the 66 patients with a RAID score <2, 92-97% met remission criteria, and 98.5% were in remission or low disease activity according to DAS28-ESR or DAS28-CRP thresholds.…”
Section: Peter C Taylormentioning
confidence: 99%
See 3 more Smart Citations